Nilai-nilai Budaya Sekolah dalam Pembinaan Aktivitas Keagamaan Siswa - Arrosyad, Muhammad Iqbal; Oktaviani, Siti Nur; Eftia, Harsela; Karisma, Nadia; Meliyana, Bella (Atthulab: Islamic Religion Teaching and Learning Journal, 2020)
The purpose of the study is to explain the schoolâ€™s cultural values in fostering religious activities. This research took place in public elementary school 5 Mendo Barat. The research method used is descriptive qualitative methods. Data collection techniques used are structured and unstructured interviews, observation, and documentation to obtain relevant data. The subjects of this study were the principal, teacher, and students. The results of this study include: 1) Inculcation of school cultural values such as shame culture, religious culture, responsibility literacy culture, and culture of respect for people who are young or older.2) Implementation 0f fostering religious activities in public elementary school 5 Mendo Barat. 3) Advantages and disadvantages of carrying out religious activities public elementary school 5 Mendo Barat is like the cultivation of religious knowledge in children from an early age is very good. This study found that school cultural values in the fostering of religious activities have been instilled early on by every teacher to students well where they have been taught religious habituation and the inculcation of school cultural values to from learners with character and noble character.Â Tujuan penelitianmenjelaskan tentang nilai-nilai budaya sekolah dalam pembinaan aktivitas keagamaan, penelitian ini mengambil lokasi di SD Negeri 5 Mendo Barat. Metode penelitian yang digunakan yakni metode deskriptif kualitatif. Teknik pengumpulan data yang digunakan yakni wawancara terstruktur dan tidak terstruktur, observasi dan dokumentasi agar memperoleh data yang relevan. subjek penelitian ini adalah kepala sekolah, guru, dan siswa. Hasil penelitian ini diantaranya: 1) Penanaman nilai-nilai budaya sekolah seperti budaya malu, budaya religious, tanggung jawab, budaya literasi, dan budaya menghormati orang yang muda maupun yang lebih tua. 2) Pelaksanaan Pembinaan aktivitas keagamaan di SD Negeri 5 Mendo Barat 3) Kelebihan dan kekurangan aktivitas keagamaan SD Negeri 5 Mendo Barat yakni seperti penanaman ilmu agama kepada anak sejak usia dini sangat baik. Penelitian ini menemukan bahwa nilai-nilai budaya sekolah dalam pembinaan aktivitas keagamaan telah di tanamkan sejak dini oleh setiap guru terhadap peserta didik dengan baik dimana telah di ajarkan pembiasaan keagamaan dan penanaman nilai budaya sekolah sehingga dapat membentuk peserta didik yang berkarakter dan berakhlak mulia.